The Internalization of Akhlakul Karimah Values at TPQ Imamul Muttaqin in Kenangkan Hamlet, Berhasil Kidul Village, Semarang Regency - Adam Wiratama Graha Saputra; Matori; Zaenal Abidin (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
Noble character (akhlakul karimah) is the main foundation in shaping students’ character in Islamic education. The cultivation of moral values is not sufficient to be carried out through the delivery of material cognitively, but requires a process of internalization that takes place continuously in daily life. Taman Pendidikan Al-Qur’an (TPQ) as a non-formal educational institution has a strategic role in fostering children’s morals through Qur’anic learning and the habituation of religious behavior. This study aims to analyze the process of internalizing akhlakul karimah values at TPQ Imamul Muttaqin, Kenangkan Hamlet, Bergas Kidul Village, Semarang Regency, and to identify the factors that support and hinder the process. The research uses a qualitative approach with a case study design. Data were obtained through observation, interviews with the head of TPQ and teachers, as well as documentation of learning activities. Data were analyzed through stages of data reduction, data presentation, and conclusion drawing to obtain a comprehensive description of the dynamics of the internalization of akhlakul karimah values in the context of non-formal education. The results show that the internalization of akhlakul karimah values is carried out through role modeling and habituation that are consistently applied in learning activities. The values instilled include honesty, discipline, responsibility, respect for teachers and parents, politeness, and a helpful attitude. The role modeling of ustaz and ustazah becomes the most dominant method because students tend to imitate the behavior of educators in daily interactions. The habituation of religious activities such as collective prayer, reading the Qur’an, maintaining proper conduct, and time discipline strengthens the practice of values in real life. The success of internalization is supported by a religious community environment and the involvement of parents in reinforcing children’s habits at home. The obstacles faced include the diversity of students’ character, the influence of digital media, and limited parental assistance. This study concludes that the internalization of akhlakul karimah values at TPQ Imamul Muttaqin takes place through the integration of role modeling, habituation, the role of the family, and the support of the social environment. Qur’an-based non-formal education has a significant contribution to the formation of children’s character when implemented consistently and continuously. These findings imply that strengthening the synergy between TPQ and the family becomes an important aspect in maintaining the sustainability of children’s moral development.